2015
DOI: 10.1556/032.65.2015.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Herd behaviour in Southeast Asian stock markets — An empirical investigation*

Abstract: This study examines herd behaviour in four Southeast Asian stock markets, namely Indonesia, the Philippines, Malaysia, and Vietnam. Empirical results indicate that except for the Philippines, herding exists in the other three markets. Stronger evidence of herding has been detected in these markets when the market is up. When the market is down, it is only the Malaysian market that exhibits signifi cant herding. The study further investigates herding by dividing the entire sample period into two sub-periods: pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Liu (2013) observed herd behavior in the Singapore capital market both throughout the financial crisis and when the market soared and collapsed, and discover the occurrence of herding tendency, especially when the market falls. Bui, Nguyen, and Nguyen (2015) conducted herding behavior research in Indonesia, the Philippines, Malaysia, and Vietnam and discovered very high herding behavior in the Indonesian and Malaysian capital markets during the pre-crisis and economic crises. Noviliya & Prasetiono (2017) checked herd behavior in the Singapore and Indonesia capital markets, study results showed that herd behavior only occurred in the Indonesia capital market.…”
Section: Literature Review Herding Behavior In Capital Marketmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu (2013) observed herd behavior in the Singapore capital market both throughout the financial crisis and when the market soared and collapsed, and discover the occurrence of herding tendency, especially when the market falls. Bui, Nguyen, and Nguyen (2015) conducted herding behavior research in Indonesia, the Philippines, Malaysia, and Vietnam and discovered very high herding behavior in the Indonesian and Malaysian capital markets during the pre-crisis and economic crises. Noviliya & Prasetiono (2017) checked herd behavior in the Singapore and Indonesia capital markets, study results showed that herd behavior only occurred in the Indonesia capital market.…”
Section: Literature Review Herding Behavior In Capital Marketmentioning
confidence: 99%
“…Most of the countries in ASEAN are still classified as emerging capital markets, merely Singapore has entered the developed capital market. A number of researchers have proven that herding behavior take place in ASEAN capital markets (Singapore, Indonesia, Malaysia, the Philippines, Thailand, Vietnam), especially when the market is under stress (Liu, 2013;Bui, Nguyen and Nguyen, 2015;Noviliya & Prasetiono, 2017;Kabir and Shakur, 2018;Rahman & Ermawati, 2019;Jirasakuldech & Emekter, 2020;Muharam, et al, 2021). Other research in ASEAN countries found no evidence of herd behavior (Kabir & Shakur, 2018;Ramadhansyah, 2020;Nimanussornkul & Nimanussornkul, 2021;Muharam et al, 2021;Ah Mand et al, 2021).…”
Section: Introductionmentioning
confidence: 99%